Multidisciplinary assessment of agricultural innovation and its impact: A case study of lowland rice variety WITA 9 in Côte d’Ivoire - Saito, Kazuki; Touré, A.; Arouna, A.; Fiamohe, R.; Silué, D.; Manful, J.; Bèye, A.; Efisue, A.A. (Informa UK Limited, 2019)
Information on comprehensive evaluation of agricultural innovations is often limited. This study provides an overview of multidisciplinary evaluation of a lowland rice variety, WITA 9 (released in Côte d’Ivoire in 1998), with respect to its agronomic performance, grain quality, resistance to diseases, adoption by farmers, impact on productivity and farmers’ income, and marketability. WITA 9 had the highest paddy yield among the tested varieties including an international check (IR 64) and recently developed varieties adapted to this country. WITA 9 had a higher amylose content (26–28%) than others tested. This study confirmed its resistance to bacterial leaf blight, Rice yellow mottle virus (RYMV), and rice blast. A household survey showed that the adoption rate was 24%, its paddy yield advantage was 0.7 t ha–1, and its adoption increased farmer’s income by US$ 91 ha–1 per season. A market study showed that consumers’ willingness to pay was higher for WITA 9 than any other locally produced rice variety and comparable to imported rice in one of two markets. We conclude that WITA 9 is an ideal innovation for enhancing productivity and rice import substitution in Côte d’Ivoire. An effective seed delivery system and enhancing farmers’ and consumers’ awareness of this variety are vital for accelerating impact.